CRITERIA FOR SELECTING VOLLEYBALL TEAM CAPTAIN ON THE SIGNS OF THEIR LEADER BEHAVIOR - Nikolaev, A.N.; Shlat, N.Yu.; Anufryienko, L.V.; Shalak, O.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the dependence of the cohesion of sports teams, the success of their performances, as well as the development of the personality of young volleyball players, on the degree of severity of the captains of these teams' propensity for various leadership options. Methods and structure of the study. In the study of the components of leadership behavior of some of the athletes, a holistic approach was used, consisting in the use of both personal and team indicators. Two methods were also used as instrumental methods - a laboratory experiment and a closed survey. The subjects were female athletes of older adolescence (13-15 years old) involved in volleyball. The study was reduced to measuring indicators of leadership behavior, the main socio-metric indicator - team cohesion, successful performances. Results and conclusions. The success of the team's performances, on the one hand, is determined by its cohesion, which, in turn, depends on the match "captain - expressive leader." The fact that the functions of the team captain and the instrumental leader coincide contributes to the competitive success of the athletes. The success of activities for the upbringing, education and rehabilitation of young female volleyball players to a certain extent depends on the level of team cohesion and on the match "captain - expressive leader". All this should be taken into account in the practical activities of trainers.